Effects of H2S and CO2 on Cement/Casing Interface Corrosion Integrity for Cold Climate Oil and Gas Well Applications. (29th August 2016) - Beck, Justin; Feng, Ruishu; Hall, Derek M.; Buyuksagis, Aysel; Ziomek-Moroz, Margaret; Lvov, Serguei N.
Abstract : Low-temperature corrosion relevant to oil and gas wells was investigated. Casing cement was exposed to brine in contact with CO2 at 4 °C and 10 MPa. Pore water was extracted from wet cement using a die press, and a cement simulated pore solution (CSPS) was developed to be used for corrosion studies. High levels of chloride similar to the original brine solution were found. The sodium content was well below that of the original brine, with the change in charge mostly balanced by an increase in dissolved calcium. The calcium content was above predictions for brine-CO2 -Ca(OH)2 equilibrium, suggesting that sodium was displaced in favor of calcium. Corrosion measurements were performed on casing steel using linear polarization resistance, electrochemical impedance spectroscopy, and mass loss samples with H2 S:CO2 ratios from 0 to 0.001. The corrosion rate was found to decrease slightly with increasing sulfide content from 0.02 to 0.01 mm y -1 .